Disparities in Access to Well-Qualified, Well-Supported Special Educators Across Higher- Versus Lower-Poverty Schools Over Time. (April 2022) - Bettini, Elizabeth; Nguyen, Tuan D.; Gilmour, Allison F.; Redding, Christopher
Scholars have documented long-standing disparities in access to well-qualified, well-supported teachers, including disparities in access to special education teachers (SETs), based on student socioeconomic status. In response, policy initiatives have aimed to incentivize teaching in higher-poverty schools. Thus, we examined changes over time in disparities between SETs' demands and resources (including internal resources, such as qualifications, and school-based resources, such as adequate materials), using multiple waves of the nationally representative Schools and Staffing Survey. We found that, by one metric, disparities in certification have closed since 2000. However, SETs in higher poverty schools are significantly more likely to work in self-contained settings than those in lower-poverty schools, and disparities in school-based resources continue to be significant, such that SETs in higher-poverty schools were significantly more likely to teach in self-contained classes, rated teacher cooperation significantly lower, and reported having significantly weaker access to material resources.